Ca2+‐dependent proteolysis of junctophilin‐1 and junctophilin‐2 in skeletal and cardiac muscle - Murphy, R. M.; Dutka, T. L.; Horvath, D.; Bell, J. R.; Delbridge, L. M.; Lamb, G. D. (The Journal of physiology, 2013)
Key points If skeletal muscle fibres are subjected to excessive activation, or stretched whilst contracting, they subsequently display long‐term reductions in their force response, apparently due in part to structural or molecular changes at the triad junction, where excitation of the surface membrane triggers Ca2+ release from the internal Ca2+ store. The changes appear to be due to excessive or prolonged increases in intracellular Ca2+ levels, which activate Ca2+‐dependent proteases known as calpains, but their target proteins are currently unknown. This study shows that excessive muscle stimulation, or directly raising intracellular Ca2+ levels, causes calpain activation in tandem with proteolysis of junctophilin, a key protein thought to hold the triad junction together. Proteolysis of junctophilin is also seen in muscle of mice with muscular dystrophy and in cardiac muscle following ischaemic damage. Proteolysis of junctophilin may be a major factor causing muscle weakness and cardiac dysfunction in a range of circumstances. Excessive increases in intracellular [Ca2+] in skeletal muscle fibres cause failure of excitation–contraction coupling by disrupting communication between the dihydropyridine receptors in the transverse tubular system and the Ca2+ release channels (RyRs) in the sarcoplasmic reticulum (SR), but the exact mechanism is unknown. Previous work suggested a possible role of Ca2+‐dependent proteolysis in this uncoupling process but found no proteolysis of the dihydropyridine receptors, RyRs or triadin. Junctophilin‐1 (JP1; ∼90 kDa) stabilizes close apposition of the transverse tubular system and SR membranes in adult skeletal muscle; its C‐terminal end is embedded in the SR and its N‐terminal associates with the transverse tubular system membrane. Exposure of skeletal muscle homogenates to precisely set [Ca2+] revealed that JP1 undergoes Ca2+‐dependent proteolysis over the physiological [Ca2+] range in tandem with autolytic activation of endogenous μ‐calpain. Cleavage of JP1 occurs close to the C‐terminal, yielding a ∼75 kDa diffusible fragment and a fixed ∼15 kDa fragment. Depolarization‐induced force responses in rat skinned fibres were abolished following 1 min exposure to 40 μm Ca2+, with accompanying loss of full‐length JP1. Supraphysiological stimulation of rat skeletal muscle in vitro by repeated tetanic stimulation in 30 mm caffeine also produced marked proteolysis of JP1 (and not RyR1). In dystrophic mdx mice, JP1 proteolysis is seen in limb muscles at 4 and not at 10 weeks of age. Junctophilin‐2 in cardiac and skeletal muscle also undergoes Ca2+‐dependent proteolysis, and junctophilin‐2 levels are reduced following cardiac ischaemia–reperfusion. Junctophilin proteolysis may contribute to skeletal muscle weakness and cardiac dysfunction in a range of circumstances.